ISOLASI DAN KARAKTERISASI Rhizobium DARI Glycine max L. DAN Mimosa pudica Linn. - Eka Sari; Anggi Nico Flatian; Zulvia Intan Sari; Eman Sulaeman (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
N availability in Indonesia is still relatively low. Various types of fertilization techniques are developed in order to reduce N losses, but the efficiency of N fertilizer use is not optimal. Therefore, biological N-belay technology is needed through Rhizobium inoculation to improve N fertilization in legume plants. This study aims to isolate and characterize Rhizobium bacteria from nodules formed in the roots of legume plants. The collection of Glycine max L. and Mimosa pudica Linn. root nodules is ashamed to be chosen from the pink root nodules. Rhizobium isolation using selective media of Yeast Extract Manitol Agar + congo red using the spread plate method. Characterization carried out, in the form of macroscopic observations, Gram staining, biochemical physiological tests, manufacturing growth curves and pathogenicity tests. The results of isolation from both plants obtained five types of Rhizobium isolates. The results of the characterization of isolates in both plants also showed the same thing, namely: bacteria have Echinulate shape when grown on sloping media, and when grown in cup media (large size, milky white, opaque (not penetrated by light, circular shape, convex elevation (convex), the surface is smooth shiny, the entire margin), including Gram negative bacteria, rod shaped, facultative anaerobic, motile, can degrade hydrogen peroxide, show positive oxidase, can ferment glucose and sucrose, grow well at pH 5 - pH 7, and not pathogenic to plants.